Can training increase the confidence of staff and volunteers in a sector with inexperienced fundraisers? Lessons learnt from the "giving to heritage" programme. Issue 4 (16th November 2017) - Webb, Mark
Abstract : The UK independent heritage sector has traditionally not been strong at fundraising. There is a perception amongst the general public that most heritage assets are supported by funds from the state, and that sectors such as children and health are more worthy of support. At a time when pressures on central and local government budgets are increasing, the need for heritage to look for sources of private funds has never been greater, yet the level of confidence and skills to achieve this goal are relatively low. A fundraising training programme tailored to the sector was delivered between 2014 and 2017 by The Heritage Alliance in partnership with the Institute of Fundraising and supported by the Heritage Lottery Fund. This paper analyses the results and explores what worked and what did not work in the programme. An emphasis on face‐to‐face training in small workshops, backed up with other training techniques, together with online resources, resulted in higher levels of fundraising skills amongst heritage fundraisers and a surprisingly high levels of actual funds raised attributable to the training programme.